Inadvertent Traumatic Fracture of Central Venous Catheter during Procurement, Transmitted Through Solid Organ Transplant - Thaer Obaid; Corinne Cricco; Ani Simka; Richard Fine; Saravanan Ramamoorthy; Radi Zaki (Case Reports in Transplantation)
Central venous catheters play a pivotal role in the perioperative support of critically ill patients. They are used for administration of fluids, vasopressors, blood products, and various medications; however, their use may be associated with serious complications, such as catheter fracture and embolization. While most data on catheter fracture embolization consist of isolated case reports, only a few studies have examined patients with central venous catheter embolism. We report a traumatic inadvertent transection of central venous catheter that migrated through a donor transplanted liver and was found to be lodged in the recipient’s right ventricle. The catheter was retrieved under fluoroscopy using a trilobed snare device.